(untitled) (Bangkok, 2001)
These all provide basic reference points on the progress, direction and magnitude of aquaculture changes and factors associated with these changs within global regional sectoral, thematic and technical perspectives.
Keywords: Nuôi trồng thủy sản,Aquaculture,Fisheries